2020
DOI: 10.1111/dmcn.14715
|View full text |Cite
|
Sign up to set email alerts
|

Adverse outcomes after major surgery in children with intellectual disability

Abstract: To evaluate outcomes after major surgery in children and adolescents with intellectual disability. METHOD We used 2004 to 2013 claims data from Taiwan's National Health Insurance programme to conduct a nested cohort study, which included 220 292 surgical patients aged 6 to 17 years. A propensity score matching procedure was used to select 2173 children with intellectual disability and 21 730 children without intellectual disability for comparison. Logistic regression was used to calculate the adjusted odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“… 61 In four studies no differences in mortality were reported, 62–64 66 and in one study children with intellectual disability had a higher risk of 30-day mortality compared with children with no intellectual disability. 70 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 61 In four studies no differences in mortality were reported, 62–64 66 and in one study children with intellectual disability had a higher risk of 30-day mortality compared with children with no intellectual disability. 70 …”
Section: Resultsmentioning
confidence: 99%
“…15 Thirteen further articles reported on postoperative outcomes. [59][60][61][62][63][64][65][66][67][68][69][70][71] The majority of articles included data relating to Down syndrome, 59-61 63-65 68 69 followed by intellectual disability, 62 67 70 developmental delay 66 and autism spectrum disorder. 71 Increased rates of complications 60 62 63 66 69 70 were reported in a number of studies.…”
Section: Postoperative Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two new reports on the surgical care of children with disabilities, using big data from administrative databases in Taiwan and the United States. 1,2 In the study by Huang et al, children with intellectual disabilities were found to have approximately double the odds of postoperative pneumonia, sepsis, and mortality. 1 Interestingly, the odds of adverse events were increased in both tertiary and non-tertiary settings.…”
mentioning
confidence: 99%
“…1,2 In the study by Huang et al, children with intellectual disabilities were found to have approximately double the odds of postoperative pneumonia, sepsis, and mortality. 1 Interestingly, the odds of adverse events were increased in both tertiary and non-tertiary settings. Children with intellectual disabilities also experienced longer stays in hospital and increased medical expenditures compared to their matched peers.…”
mentioning
confidence: 99%